Efficacy of two anti-HIV treatment schemes at the Central Military Hospital - Sotelo Novoa, Luis Alberto (2019)
Objective: To determine the efficacy of two anti-HIV treatment schemes at the Central Military Hospital during the period from October 2017 to May 2018. Materials and methods: This was an observational, descriptive, cross-sectional and retrospective study, where the sample size was 52 patients. Central Military served during the period from October 2017 to May 2018. Results: The results showed that between the two antiretroviral schemes (INTR + IP and INTR + INNTR) both caused an increase in the CD4+ cell count but the most effective therapy was the antiretroviral regimen (INTR + INNTR) obtaining a final result of CD4+ cells higher than 500 cells/mL. Conclusion: It is concluded that the treatment (INTR + INNTR) is more effective than the (INTR + IP) in patients with HIV infection in the Central Military Hospital, being the great majority of the male sex and with basis studies with a age range of 29 and 38 years old.